2008
DOI: 10.1080/01421590802232842
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural medical education: Can patient-centered cultural competency training be effective in non-Western countries?

Abstract: Background-No evidence addresses the effectiveness of patient-centered cultural competence training in non-Western settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Several models for cultural competence training have been developed in Western countries, 3,4 and the current pedagogy embraces a patient-centered approach that focuses on evaluating individual patients and considers the unique cultural and social factors that affect their care. 57 Although several studies have demonstrated the immediate effectiveness of this patient-centered cultural competence training approach in controlled trials in many Western and a few Eastern countries, 4,810 we could find no evidence in the medical literature evaluating the long-term effectiveness of this strategy. 11 …”
mentioning
confidence: 78%
“…Several models for cultural competence training have been developed in Western countries, 3,4 and the current pedagogy embraces a patient-centered approach that focuses on evaluating individual patients and considers the unique cultural and social factors that affect their care. 57 Although several studies have demonstrated the immediate effectiveness of this patient-centered cultural competence training approach in controlled trials in many Western and a few Eastern countries, 4,810 we could find no evidence in the medical literature evaluating the long-term effectiveness of this strategy. 11 …”
mentioning
confidence: 78%
“…Indeed, researchers have observed that patient welfare and patient autonomy are among the most common aspects of medical humanities practised by Taiwanese interns . In recent years, patient‐centred cultural competence training has been introduced, and might have impacted on students’ conceptions of professionalism …”
Section: Discussionmentioning
confidence: 99%
“…46 In recent years, patient-centred cultural competence training has been introduced, and might have impacted on students' conceptions of professionalism. 12,47 In Sri Lanka, the dominant dimension of professionalism as rules, could be partly explained by British colonial and Commonwealth history, as this dimension was also dominant in Welsh, English and Australian data. In Sri Lanka, for example, medical education is considerably influenced by structures and identities imparted during the colonial period.…”
Section: Discussion Of Key Findings In Light Of Existing Theory and Lmentioning
confidence: 99%
“…It is important to take national and regional cultural differences sufficiently into account when disseminating educational theories [14, 15]. The style of communication in East Asia is sometimes described as “cultural reticence,” which consists of a reluctance to speak and a tendency not to express as much as is known or felt [16].…”
Section: Discussionmentioning
confidence: 99%